IMPLEMENTATION OF VOCATIONAL PROGRAMS IN ENHANCING STUDENTS’ SKILLS IN GRAPHIC ENGINEERING AND CULINARY ARTS AT MADRASAH ALIYAH - Abdurokhman; Senowarsito; Harto Nuroso (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the implementation of vocational programs in enhancing students’ skills in Graphic Engineering and Culinary Arts at Darul Ulum Islamic Senior High School (Madrasah Aliyah Darul Ulum) Purwogondo, Jepara. The study employed a qualitative approach with a case study design. The research participants included the school principal, vice principal, vocational program teachers, students, and alumni, who were selected purposively. Data were collected through interviews, observations, and documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation, as well as member checking. The findings indicate that the implementation of vocational programs has been carried out systematically through the stages of planning, organizing, implementation, and evaluation, which are integrated into the school curriculum. Project-based and production-based learning effectively enhance both technical skills (hard skills) and non-technical skills (soft skills), such as discipline, teamwork, and self-confidence. The vocational programs also improve students’ work readiness and entrepreneurial mindset. The success of the program is supported by adaptive school leadership and the utilization of social capital, although challenges remain in terms of facilities and infrastructure.